Effect of wildfires on tropical peatland vegetation in Meranti Islands District, Riau Province, Indonesia - Sinta Silviana; BAMBANG HERO SAHARJO; SIGIT SUTIKNO (Society for Indonesian Biodiversity, 2019)
Abstract. Silviana SH, Saharjo BH, Sutikno S. 2019. Effect of wildfires on tropical peatland vegetation in Meranti Islands District, Riau Province, Indonesia. Biodiversitas 20: 3056-3062. Wildfires are one of the main causes of forest destruction, disturbing forest sustainability. Wildfires are mainly caused by human activities, such as land clearing, wood harvesting, draining, etc. Wildfires could induce the loss of vegetation. This study was aimed at assessing the effect of wildfires on both vegetation biomass and necromass on coastal peatland ecosystems in Sungaitohor Village, Tebing Tinggi Timur Sub-district, Meranti Islands District, Riau Province, Indonesia. Analysis of vegetation and both above and below the ground biomass composition were performed. The approach used a paired sample with 4 replications (n = 4 burnt, n=4 unburnt). The variables observed in every research sites was analyzed using Student-T test. Models were generated and then validated to understand the effect of fires on biomass. The results showed that there was a significant difference in the studied parameters between the unburned area and burned area (P <0.01). Wildfires affected the quantity of living plants (biomass) which was indicated by the fact that biomass is unburnt and burnt areas were in the ratio of 2.67 : 1. The quantity of dead plants (necromass) was greater in the burned plots than in the unburnt plots. All these findings suggest that high intensity of forest fires had occurred in the study sites.